Comparative study on calculation methods of dam-break wave. Issue 5 (3rd September 2019) - Yang, Shaolin; Yang, Wanli; Qin, Shunquan; Li, Qiao
ABSTRACT: This paper presents systematic comparisons of dam-break wave generation and propagation between numerical solutions of RANS equations with three different turbulence models (standard k – ε, RNG k – ε and k – ω ), numerical solutions of Euler equations, analytical solutions and experimental data from literature for both dry-bed and wet-bed cases. Results show that numerical solutions of RANS equations with the three different turbulence models can accurately calculate the whole process of dam-break wave propagating over both dry-bed and wet-bed. Numerical solutions of Euler equations show remarkable discrepancies compared with the experimental data in dry-bed condition, but can predict the dam-break wave well in wet-bed conditions. The merits and demerits of the calculation methods are discussed in full and their application scopes are suggested.